DOUBLE UPDATING OF PHRASEOLOGICAL UNITS - Jabbarova, Anora (Журнал иностранных языков и лингвистики, 2021)
This article is about double updating of phraseological units. It analyzes the use of stylistic techniques and the use of phraseological units. This article is based on the potential to isolate an element of a phraseological unit as an independent semantic unit, since each word, based on a component of a phraseological phrase, acquires a dual essence.